White Paper: A Multidimensional Understanding of Effective University and College Counseling Center Organizational Structures. Issue 2 (3rd April 2019) - Mitchell, Sharon L.; Oakley, Danielle R.; Dunkle, John H.
ABSTRACT: Established in 1950, the Association for University and College Counseling Center Directors (AUCCCD) is an international organization comprising universities and colleges (https://www.aucccd.org). AUCCCD members are the higher education leaders for student mental health. Our members represent a wide range of professional disciplines, public and private institutions, and a range of institutional student enrollment sizes. This white paper: (a) provides a historical background on counseling and mental health services on college campuses; (b) argues that, based on current research, there is no single organizational structure that is optimal; (c) makes recommendations about factors to consider when making decisions about the counseling center that are based on specific campus needs and resources rather than a preferred organizational structure; and (d) advocates for a collaborative care model regardless of organizational structure.